2007
DOI: 10.3168/jds.2007-0359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short Dry Periods on Performance and Metabolic Status in Holstein Dairy Cows

Abstract: To evaluate effects of different dry period lengths on milk yield, milk composition, and energy balance of dairy cows, 122 multiparous and primiparous Holstein dairy cows were used in a completely randomized experimental design with 56-, 42-, and 35-d dry period lengths. Actual dry period lengths for respective treatments (TRT) were 56 +/- 5.1 d, 42 +/- 2.1 d, and 35 +/- 2.7 d. Overall, cows in the 42- and 56-d TRT gained more body condition than those in 35-d TRT during the dry period; however, postpartum bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
124
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(157 citation statements)
references
References 31 publications
24
124
8
1
Order By: Relevance
“…Although some recent studies have demonstrated small (3.6%) or no decrease in milk production following SDP with or without recombinant bovine somatotropin (rbST) supplementation in dairy cows (Schairer, 2001;Bachman, 2002;Gulay et al, 2003), most recent studies support the previous demonstration of milk yield depression in cows with SDP Pezeshki et al, 2007 andWatters et al, 2008). Discrepancies between studies reporting an effect of SDP on subsequent milk production may arise from a multitude of factors, such as differences in parities, management schemes, genetic potential for milk production, breed, experimental models (between-cow, within-cow or half-udder model) and the number of cows used in a specific study (statistical power).…”
Section: Impact On Milk Yieldmentioning
confidence: 83%
See 3 more Smart Citations
“…Although some recent studies have demonstrated small (3.6%) or no decrease in milk production following SDP with or without recombinant bovine somatotropin (rbST) supplementation in dairy cows (Schairer, 2001;Bachman, 2002;Gulay et al, 2003), most recent studies support the previous demonstration of milk yield depression in cows with SDP Pezeshki et al, 2007 andWatters et al, 2008). Discrepancies between studies reporting an effect of SDP on subsequent milk production may arise from a multitude of factors, such as differences in parities, management schemes, genetic potential for milk production, breed, experimental models (between-cow, within-cow or half-udder model) and the number of cows used in a specific study (statistical power).…”
Section: Impact On Milk Yieldmentioning
confidence: 83%
“…However, a 30-day SDP in multiparous cows has often been shown to have no impact on subsequent milk yield. When the additional 30 days of production in the previous lactation are included in the milk yield estimate there is often a production advantage for use of 30-day SDP in multiparous cows (Annen et al, 2004a;Pezeshki et al, 2007 and.…”
Section: Impact On Milk Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortening the dry period to 28 -35 days also resulted in a statistically significant milk yield loss (-1.4 kg/d). Milk yield loss as a result of dry period reduction was reported to be stronger for primiparous cows than for multiparous cows (Annen et al, 2004, Pezeshki et al, 2007. Cows without a dry period were reported to produce approximately 800 -1200 kg milk during the last 56 -60 days of lactation (Schlamberger et al, 2010, Annen et al, 2004.…”
Section: Energy Balance Milk Production and Compositionmentioning
confidence: 99%